The place of nonsteroidal anti-inflammatory drugs in the current osteoarthritis guidelines - E. A. Taskina (Современная ревматология, 2020)
The paper provides a review of the data available in the literature on the relationship of pain to the risk of OA progression. Network analyses and numerous studies, including those conducted at the V.A. Nasonova Research Institute of Rheumatology, have confirmed that pain syndrome is one of the significant predictors of knee OA progression. The major class of medications for OA pain includes nonsteroidal anti-inflammatory drugs. The paper gives data on the efficacy of meloxicam in OA patients, which is widely used in both Russia and other countries of the world. Meloxicam is characterized by a good safety profile in the gastrointestinal tract, cardiovascular and renal systems. It is the drug of choice in patients with musculoskeletal diseases, in particular OA. Good results in severe pain syndrome have been shown by a step-by-step regimen of meloxicam when the injection formulation of the drug is used in the first days of treatment, and then, to consolidate what has been gained from therapy, its oral dosage form is administered in terms of concomitant diseases.